Influence of Femtosecond Laser Surface Modification on Tensile Properties of Titanium Alloy - Kai Zhou; Xiaoyuan Nie; Xingbang Che; Han Xiao; Xuwen Wang; Junming Liao; Xu Wu; Can Yang; Chunbo Li (Micromachines, 2024)
Titanium alloy components often experience damage from impact loads during usage, which makes improving the mechanical properties of TC4 titanium alloys crucial. This paper investigates the influence of laser scanning irradiation on the tensile properties of thin titanium alloy sheets. Results indicate that the tensile strength of thin titanium alloy sheets exhibits a trend of initial increase followed by a decrease. Different levels of enhancement are observed in the elongation at break of a cross-section. Optimal improvement in the elongation at break is achieved when the laser fluence is around 8 J/cm2, while the maximum increase in tensile strength occurs at approximately 10 J/cm2. Using femtosecond laser surface irradiation, this study compares the maximum enhancement in the tensile strength of titanium alloy base materials, which is approximately 8.54%, and the maximum increase in elongation at break, which reaches 25.61%. In addition, the results verify that cracks in tensile fractures of TC4 start from the middle, while laser-induced fracture cracks occur from both ends.